2005
DOI: 10.1103/physrevb.72.245208
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of molecular dimers inα-PTCDA byab initiomethods: Binding energies, gas-to-crystal shift, and self-trapped excitons

Abstract: Time-dependent density functional theory ͑TD-DFT͒, Hartree-Fock, second-order Møller-Plesset perturbation theory ͑MP2͒, and configuration interaction of singly excited states ͑CIS͒ are applied to crystalline PTCDA ͑3,4,9,10-perylene tetracarboxylic dianhydride͒. The systems investigated include single molecules in an optimized rectangular shape, and molecules and molecular dimers compatible with the experimental geometry in the crystalline ␣-phase. Total energy calculations for pairs of adjacent molecules resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 77 publications
(155 reference statements)
2
34
1
Order By: Relevance
“…The first transition is a HOMO-LUMO one at 2.43 eV with an oscillator strength of 0.76. This compares well to other published results obtained with the same method [6,7]. Within the Born-Oppenheimer approximation, the nuclei are brought into a vibronic level of the excited molecule after absorption of light.…”
Section: Experimental Methodssupporting
confidence: 87%
“…The first transition is a HOMO-LUMO one at 2.43 eV with an oscillator strength of 0.76. This compares well to other published results obtained with the same method [6,7]. Within the Born-Oppenheimer approximation, the nuclei are brought into a vibronic level of the excited molecule after absorption of light.…”
Section: Experimental Methodssupporting
confidence: 87%
“…Previous optical studies of PTCDA have shown that Frenkel excitons and CT states mix only weakly, so that they result in quite different features in photoluminescence, 21,27,28 an interpretation corroborated by the small values of the transfer parameters t e and t h . PTCDA is one of the exceptional cases where information on the anisotropy of the optical response is available, 22,61 and in contrast to DIP, 32 the large angle between the transition dipoles of the two basis molecules yields oscillator strengths of similar size for both components of the dielectric tensor; compare Tables V and VI.…”
Section: A Ptcdamentioning
confidence: 90%
“…Therefore, PL bands arising from self-trapped CT states occur below recombination from the dispersion minimum of the lowest dispersion branch of the Frenkel exciton, E 00 F ͑k͒. 21,27,28 Moreover, weak transitions around 1.95 eV and 2.12 eV arising from E 00 CT and E 01 CT , respectively, allow the selective excitation of PL from CT states. 9,65 The value of E 00 CT = 1.95Ϯ 0.07 eV deduced from the Frenkel-CT model corresponds to an average CT transition energy of ͗E CT ͘ = E 00 CT + ͑S + + S − ͒ប = 2.12Ϯ 0.07 eV, in good agreement with an earlier estimate based on excimer PL arising from a selftrapped CT exciton modeled as a deformed dimer, indicating a value in the range ͗E CT ͘ = 2.14Ϯ 0.08 eV for the undeformed crystal.…”
Section: A Ptcdamentioning
confidence: 99%
See 2 more Smart Citations